Canadian STI national goals and phase specific strategies. (1st April 2002) - Wong, T; Sutherland, D
Abstract : National goals should be "SMART"—specific, measurable, achievable, resource sensitive, and timed. To be meaningful, these goals must be sustainable and realistic within the time frame and fiscal limitations. Multisector partnerships are essential for the goals to become operational.